Reporting of Race and Ethnicity in the Ophthalmology Literature in 2019 - Moore, Daniel B. (JAMA Ophthalmol, 2020)
IMPORTANCE: The description of racial and ethnic data in human trials is relatively unregulated, leading to potential confusion with and inconsistent reporting of these data. OBJECTIVE: To determine the frequency and use of racial and ethnic data in the ophthalmology literature in 2019. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study included all full-length human studies published between January and December 2019 in the American Journal of Ophthalmology, JAMA Ophthalmology, and Ophthalmology. MAIN OUTCOMES AND MEASURES: Whether race or ethnicity was included in the data or analysis, how the categorization was described in the methods and results, specific racial and ethnic categories used, and whether and how the categories were determined. RESULTS: A total of 547 articles were identified during the study period, 484 (88% ± 2.7%) of which reported background demographic information, including patient age and sex. Only 233 (43% ± 4.1%) reported race and/or ethnicity. Of those articles, 72 (31% ± 5.9%) categorized it as race, 51 (22% ± 5.3%) ethnicity, 56 (24% ± 5.4%) race/ethnicity, 21 (9% ± 3.7%) race and ethnicity, 12 (5% ± 3.0%) descent, 12 (5% ± 2.9%) population, and 5 (2% ± 2.0%) ancestry; in 21 (9% ± 3.8%) it was not defined. Only 30 studies (13% ± 4.4%) described how it was determined in the methods or results, most frequently by self-report (77% ± 3.9%). A total of 78 races and/or ethnicities were defined. CONCLUSIONS AND RELEVANCE: While most articles during the study period reported background demographic information, few included race and ethnicity and only a fraction of those described how these data were determined. The categories used were heterogeneous and often inconsistent. These findings suggest the need for increased and more standardized reporting of ethnic and racial demographic data in the ophthalmology literature.